Toksisitas moluskisida niklosamida terhadap pertumbuhan dan kondisi histopatologi juwana ikan mas (Cyprinus carpio) [Toxicity of molluscicide niclosamide on growth and histopathology condition of juvenile common carp (Cyprinus carpio] - Eddy Supriyono; Yosmaniar Yosmaniar; Kukuh Nirmala; Sukenda Sukenda (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
Niclosamide (2', 5- dichloro-'4 nitrosalicylanilide) as pesticide is extensively used for eliminating golden apple snail (Pomacea sp.) in paddy field. This study aimed to determine effect of sublethal molluscicide niclosamide toxicity on the growth and histopathology condition of juvenile common carp (Cyprinus carpio). This research was conducted at Research Station for Environment and Toxicology, BPPBAT Bogor. The research used sixteen glass aquariums of 70 cm x 50 cm x 60 cm in size with 40 L water volume, equipped with aeration system and stocked with 20 juveniles per each aquarium. Fish were fed to apparent satiation during the treatment and water exchange for every 48 hours. Research design was completely experimental randomized with four treatments and four replications of different niclosamide concentrations i.e. 0.00; 0.01; 0.03; 0.05 mg L